Cellulose Nanopaper and Nanofoam for Patient‐Tailored Drug Delivery. Issue 9 (15th February 2017) - Löbmann, Korbinian; Wohlert, Jakob; Müllertz, Anette; Wågberg, Lars; Svagan, Anna J.
Abstract : The development of drug delivery systems with tailored drug release can be very challenging especially in the case of problematic drugs. To address this problem, pharmaceutical scientists frequently use different formulation approaches and excipients, often involving a complex and multistep preparation. In this study, new cellulose nanofiber (CNF) based drug formulations are developed that allow controlled drug release in a facile and fast way, i.e., by simply casting drug/CNF dispersions. Altering the processing conditions and utilizing the unique inherent chemicophysical properties of cationic CNF at interfaces, it is possible to produce either drug‐loaded CNF nanopapers (containing 21 or 51 wt% drug) or nanofoams (containing 21 wt% drug). The different formulations exhibit tailored release kinetics of the poorly water‐soluble model drug indomethacin from immediate (nanopapers, 10–20 min) to slow release (nanofoams, ≈24 h). The fast release, from the nanopapers, is a result of the interplay of the molecular and supramolecular structure of indomethacin in addition to observed enhanced intrinsic dissolution of drug in the presence of CNF. The slower drug release is achieved by changing the hierarchical structure, i.e., creating a CNF based foam (porosity 99.2 wt%), and the prolonged release is mainly due to an extended drug diffusion path. Abstract : New types of drug delivery systems, i.e., nanopaper and nanofoam, are prepared in facile way by utilizing cellulose nanofibers (CNF) and drug only. The nanofoam is a result of the interaction and interfacial behavior of CNF and drug. The different formulations exhibit tailored drug release kinetics ranging from immediate (nanopapers, 10–20 min) to slow release (nanofoams, ≈24 h).